Sur les points singuliers et la convergence des series de Dirichlet avec les exposants complexes - Tourpanova, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. М. Турпанова. Об особых точках и сходимости рядов Дирихле с комплексными показателямиV. Turpanova. Dirichle eilučių kompleksiniais rodikliais pavieniai taškai konvergavimas